Tiger, Tiger : A Memoir - Fragoso, Margaux (London 2011)
I still think about Peter, the man I loved most in the world, all the time. We were friends, soul mates and lovers. I was seven. He was fifty-one.
Keywords: Sexually Abused Girls -- United States -- Child Molesters